THE ANALYSIS OF THE STRUCTURE INFLUENCE AND THE FINANCIAL BALANCE OF ECONOMIC RENEWABILITY IN THE HOTEL-RESTAURANT SECTOR IN DOLJ REGION - Dorobanțu Alin Ionuț; Dumitrescu Ioan Alexandru (Annals of the University of Craiova: Economic Sciences Series, 2018)
Research work starts, in its study, from the analysis of the correlation between economic profitability indicators of capital structure and financial stability. After checking the correlations, based on the form of the expression rate economic profitability of capital, we have created a model of factorial analysis. Thus, using the French model DuPont, we obtained a model as the product of the factors that is made up of both financial and structural indicators of financial stability. The level and dynamics of the economic rate of return under the influence of these factors was followed by the calculation of the 15 companies in the hotels-restaurants in Dolj County, the analyzed period 2013 - 2014. The method of the financial analysis is the method applied in the paper chain substitution